Inovação tecnológica e direitos fundamentais: uma análise da Lei do Bem e sua eficácia - Guimarães, Olivia Oliveira (2024)
Innovation is an indispensable component of economic and social development, and is recognized as a fundamental right in many contexts. In Brazil, public policies that encourage innovation, such as the Lei do Bem, play an essential role in promoting this right. This dissertation explores the benefits of the Lei do Bem, analyzing its historical evolution, its requirements, and its applicability. The first chapter investigates the right to innovation as a fundamental right, highlighting the importance of tax incentives to promote the social function of innovation. The historical evolution of innovation in Brazil and related public policies are examined, contextualizing the role of the Lei do Bem in the national panorama. The second chapter presents an analysis of innovation theories, with emphasis on Schumpeter's theory and the quadruple helix theory. In addition, a case study of the Technology Park of the University of Passo Fundo is carried out, illustrating the practical application of these theories in a specific context. The third chapter discusses the impacts of innovation, especially with regard to tax incentive policies, in promoting global sustainability. Indicators of the Lei do Bem are analyzed for the period 2019 to 2022, providing information on its effectiveness and scope. It is worth noting that it is part of the research line Constitutional Jurisdiction and Democracy, with its area of ​​concentration being New Paradigms of Law, of the Stricto Sensu Postgraduate Program - Master's Degree in Law of the School of Legal Sciences of the University of Passo Fundo. Considerations on the sustainability and continuity of tax incentive policies for innovation in Brazil are raised, together with an analysis of how innovation impacts the competitiveness of nations in a global context. This study contributes to an understanding of the role of innovation and tax incentive policies in promoting economic development and sustainability.